2013
DOI: 10.5812/hepatmon.10134
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Occult Hepatitis B Virus in Plasma and Peripheral Blood Mononuclear Cell Compartments of Patients WithChronic Hepatitis C Infection in Tehran-Iran

Abstract: BackgroundOccult hepatitis B virus (HBV) infection (OBI) is frequently reported in patients with chronic hepatitis C virus (HCV) infection. An association between OBI and more liver damage, cirrhosis, hepatocellular carcinoma, and reduced response to interferon therapy in patients with HCV infection is suggested.ObjectivesThe aim of this study was to determine the prevalence of occult HBV, and evaluate its clinical influence on patients with chronic HCV.Patients and MethodsA cohort study including50 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…Therefore, in order to find out whether the PBMCs are capable of transmitting the virus in CHD patients and KTxR, we performed additional testing for HBV DNA in PBMC in all patients. However, in contrast to the above‐mentioned studies, we did not detect HBV DNA in PBMC in any of our CHD or KTxR cohorts. The testing for HBV DNA in PBMCs was less sensitive than testing in serum in our study, with only positive tests in PBMCs being in the HBsAg+, non‐CHD and non‐KTx control group.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, in order to find out whether the PBMCs are capable of transmitting the virus in CHD patients and KTxR, we performed additional testing for HBV DNA in PBMC in all patients. However, in contrast to the above‐mentioned studies, we did not detect HBV DNA in PBMC in any of our CHD or KTxR cohorts. The testing for HBV DNA in PBMCs was less sensitive than testing in serum in our study, with only positive tests in PBMCs being in the HBsAg+, non‐CHD and non‐KTx control group.…”
Section: Discussioncontrasting
confidence: 99%
“…Additional testing for HBV DNA in PBMCs has been suggested to uncover occult infections not detected by serologic methods or virus determination in serum, avoiding the potential risk of a liver biopsy . Though the existence of HBV in extrahepatic tissue had been debated controversially, there is evidence that HBV can infect and replicate in PBMCs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HBV is generally considered to be hepatotropic, HBV specific nucleic acids and relative antigen can be detected in many extrahepatic tissues (20,21), and it has been proved that PBMC may be the extrahepatic place of HBV transcription and translation (22,23). In the present study, 15 mothers and 7 neonates were positive for HBV cccDNA in PBMC, which suggested that HBV can exist and be replicated in PBMC.…”
Section: Discussionmentioning
confidence: 52%
“…The OBI prevalence in chronic HCV patients was 45.7% (42/92) in Morocco[25] and 20% (18/50) in Iran[26], while none of 100 Portuguese patients showed serum OBI[19]. A retrospective study in Taiwan showed that serum OBI prevalence as determined by nested PCR using 3 sets of primers in patients with chronic HCV infection was 14.8% (31 of 210), which did not differ from that of healthy controls (15%, 15/100), and the prevalence of OBI did not parallel the severity of liver disease (14.5% in chronic hepatitis, 8% in liver cirrhosis, and 22% in HCC)[27].…”
Section: Discussionmentioning
confidence: 99%